2006
DOI: 10.1111/j.1365-2621.2005.01096.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the glass transition and storage temperature of frozen peas on the loss of quality attributes

Abstract: Green peas of two different maturities were used to evaluate the influence of the glass transition temperature (Tg¢) and storage temperatures on quality loss during frozen storage. Young peas which have a lower tenderness rating (TR) value, possibly with less starch and higher sugar content than old peas, gave a lower Tg¢ value. Quality attributes, including green colour and vitamin C, were measured over time when the peas were stored at )5, )12, )20, )25 and )30°C, respectively. The results indicated that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Frozen peas should be stored at temperatures lower than the Tg. The glass transition temperature of frozen green peas was investigated by Lim et al (2006) and found to be -20 °C for old peas (with a TR of 141) and -26 °C for younger peas (with a TR of 99). The older peas most likely have a higher Tg than the younger peas because they have less juice quantity and are hence more stable at higher freeze temperatures.…”
Section: Temperature Abuse and Storagementioning
confidence: 99%
“…Frozen peas should be stored at temperatures lower than the Tg. The glass transition temperature of frozen green peas was investigated by Lim et al (2006) and found to be -20 °C for old peas (with a TR of 141) and -26 °C for younger peas (with a TR of 99). The older peas most likely have a higher Tg than the younger peas because they have less juice quantity and are hence more stable at higher freeze temperatures.…”
Section: Temperature Abuse and Storagementioning
confidence: 99%
“…As the storage temperature is increased above the glass transition temperature, the amount of unfrozen water mobilizing solutes in the viscous matrix increases. Hence, the increase in mobility of solutes permits enzymic and oxidation reactions to continue, which increases degradation in the product during frozen storage (Lim et al 2006).…”
Section: Storage Stabilitymentioning
confidence: 99%
“…This temperature depends on vegetables type, e.g. it is around À26 and À20°C for young and old peas, respectively (Lim et al, 2006), and À32°C for pumpkin (Gonçalves et al, 2007a). The glass transition temperature is a time dependent change on the physical state.…”
Section: Introductionmentioning
confidence: 99%